Caudal duplication syndrome: a rare entity - Kanwal, Saadia; Batool, Shazia; Naqvi, Shamoona; Israr, Naila; Akhtar, Samina; Zia, Saadia (Journal of the Pakistan Medical Association, 2024)
The rare caudal duplication syndrome is a spectrum of anomalies primarily involving partial or complete duplication of organs comprising the gastrointestinal, genitourinary and distal neural tube systems. These findings are considered to be a result of aberrant embryogenesis. We hereby report a case of an adult female with complete duplication of the genital and urinary systems (urethra and bladder), hindgut and lower end of vertebral column with no functional impairment. She presented in her first pregnancy at 36 weeks gestation, in labour. To the author’s knowledge this is the first case of caudal duplication syndrome with pregnancy from Pakistan. Key Words: Caudal duplication, Genitourinary, Gestation, Hindgut.